Touch-mode capacitive pressure sensor with graphene-polymer heterostructure membrane. (30th November 2017) - Berger, Christian; Phillips, Rory; Pasternak, Iwona; Sobieski, Jan; Strupinski, Wlodek; Vijayaraghavan, Aravind
Abstract: We describe the fabrication and characterisation of a touch-mode capacitive pressure sensor (TMCPS) with a robust design that comprises a graphene-polymer heterostructure film, laminated onto the silicon dioxide surface of a silicon wafer, incorporating a SU-8 spacer grid structure. The spacer grid structure allows the flexible graphene-polymer film to be partially suspended above the substrate, such that a pressure on the membrane results in a reproducible deflection, even after exposing the membrane to pressures over 10 times the operating range. Sensors show reproducible pressure transduction in water submersion at varying depths under static and dynamic loading. The measured capacitance change in response to pressure is in good agreement with an analytical model of clamped plates in touch mode. The device shows a pressure sensitivity of 27.1 ± 0.5 fF Pa −1 over a pressure range of 0.5 kPa–8.5 kPa. In addition, we demonstrate the operation of this device as a force-touch sensor in air.